The history of language learning and teaching in Britain - McLelland, Nicola (Taylor & Francis, 2018)
This article provides an introduction, based on the most recent research available, to the history of language learning and teaching (HoLLT) in Britain. After an overview of the state of research, I consider which languages have been learnt, why and how that has changed; the role of teachers and tests in determining what was taught; changes in how languages have been taught (and why); and the emergence of the modern infrastructure of language teaching policy and practice. I conclude with case study of the contribution of Walter Rippmann, a key figure, in the period 1895 to ca. 1920, a time of professionalisation of language teaching and of efforts towards innovation and change, which set the agenda for many of the major developments of the twentieth century, including a call for scientifically based language teaching and a greater emphasis on the spoken language.